In Praise of Divided Government - Richard A. Epstein (Washington University Law Quarterly, 1990)
In my view, you measure the success or failure of government, not by the volume of legislation that it generates, but by whatever increment of good it adds to human welfare, or as is typically the case, by the relatively small level of harm it inflicts upon social institutions. The correct way to look at things is with the strong presumption that the more legislation you have, the worse that government works.